No-till - Berhongaray, Gonzalo (2021)
No-till can often increase soil carbon, soil quality and function, and reduce CO2 emissions when compared to conventional tilling practices. Soil microbial biomass increases (+37 percent), including both fungal (+31 percent) and bacterial biomass (+11 percent), in top 20-cm soils under no-till agro-ecosystems, but not in sandy soils. No-till increased wet aggregate stability by 1 to 97 percent, water infiltration by 17 to 86 percent, and available water by 44 percent. In some studies, however, no changes in SOC, aggregate stability or water infiltration have been found.